Could Egeria have seen the “Parthenion” sea from the Top of Mount Sinai? The Landscape Visibility from the Top of Mount Sinai climbed by Egeria - Crosilla, Fabio (Archeomatica, 2023)
At the meeting organized in Novara (Italy) by the Nuova Regaldi, on September 22nd 2022, entitled “The Emmanuel Anati’s exodus proposal according to the publication of the Ennateuch in the holy language of Jerusalem Sanctuary”, during my presentation I mentioned the book “Diary of a Pilgrimage”, by the IV century AD Spanish pilgrim Egeria. In this book, among other, she describes, with wealth of details, her climb to the top of Mount Sinai. In the subsequent discussion session, two hypotheses raised about the location of Mount Sinai climbed by Egeria: Gebel Musa, in the South of the Sinai Peninsula and Har Karkom, in the Negev desert, proposed some decades ago by Emmanuel Anati, as an alternative location hypothesis of Mount Sinai. In the following, considering the description offered by Egeria about the landscape visibility from the top of mount Sinai, an objective comparison on the two hypotheses (Gebel Musa and Har Karkom) will be carried out, so to define in a scientific way, the most probable location of the Mount Sinai described by the Spanish pilgrim.